Continuing Education for Public Administrators in Special Education: Local Policy for School Inclusion - Jesus, Denise Meyrelles de; Pantaleão, Edson; Almeida, Mariangela Lima de (Education Policy Analysis Archives, 2015)
It reports the research-training process through collaborative critical action research, carried out in 2011 by the team of research Special Education: professional training, pedagogical practice and school inclusion policy, which results from a partnership between the Federal University of Espírito Santo and Espírito Santo Secretariat of Education, Brazil along with public special education administrators. This venture aimed at integrating the continuing education process from the school inclusion perspective. Based on recent research results, it discusses question about the education of special education target students, who, according to Brazilian laws, are individuals with disabilities, pervasive developmental disorders or high-potential/gifted learners. It concludes that the reflection- action-critic process instituted by the study research-training allowed a) administrators of actions aiming special education to visualize their knowledge-action and, based on group actions, institute, organize and/or reorganize managing methods that became central to local policies integrated with state and national policies; b) team work between the university and local groups as a means to overcome conflicts, stress and challenges posed to emancipation of education of individuals; c) production of contributions to epistemological changes in local policies and in the modus operandi of the public special education administrator.